Quercus ngochoaensis (Fagaceae), a new species from Ba Vi National Park, northern, Vietnam - Hoàng, Thị Bình (2023)
A new species of Quercus (Fagaceae), Q. ngochoaensis, from Ba Vi National Park, Ha Noi, northern Vietnam is described and illustrated. This species is morphologically similar to Q. glauca in having glabrous twigs, cuneate leaf base, two or three fruits per infructescence, almost entire margin of lamellate rings on cupule except the lowest three rings, slightly convex scar at the base of a nut. However, it differs from Q. glauca in having smaller leaves, cup-shaped cupule enclosing 1/2–2/3 of the nut, 7–8 lamellate rings on cupule, and subglobose nut. In addition to the description, DNA barcodes of the two partial plastid regions of matK, rbcL and the nuclear region of ITS of the new species are provided.